Desenvolvimento de uma planta piloto para estudos de poços de petróleo produzindo por plunger lift - Fonsêca, Diego Antônio de Moura (2011)
This document proposes to describe a pilot plant for oil wells equipped with plunger lift. In addition to a small size (21,5 meters) and be on the surface, the plant s well has part of its structure in transparent acrylic, allowing easy visualization of phenomena inherent to the method. The rock formation where the well draws its pilot plant fluids (water and air) is simulated by a machine room where they are located the compressor and water pump for the production of air and water. To keep the flow of air and water with known and controlled values the lines that connect the machine room to the wellhole are equipped with flow sensors and valves. It s developed a supervisory system that allows the user a real-time monitoring of pressures and flow rates involved. From the supervisor is still allowed the user can choose how they will be controlled cycles of the process, whether by time, pressure or manually, and set the values of air flow to the water used in cycles. These values can be defined from a set point or from the percentage of valve opening. Results from tests performed on the plant using the most common forms of control by time and pressure in the coating are showed. Finally, they are confronted with results generated by a simulator configured with the the pilot plant s feature